2020
DOI: 10.2174/1381612826666200128095248
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Multi-Target Compounds: A Special Emphasis on their Potential as Chemo-adjuvants in Cancer Therapy

Abstract: : Flavonoids are low molecular weight, polyphenolic phytochemicals, obtained from secondary metabolism of various plant compounds. They have a spectrum of pharmacological efficacies, including potential anticancer efficacy. Natural flavonoids are present in fruits, vegetables, grains, bark, roots, stems, flowers, tea and wine. Flavonoids can attenuate or inhibit the initiation, promotion and progression of cancer by modulating various enzymes and receptors in diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 148 publications
1
12
0
Order By: Relevance
“…However, further progress in precision medicine in the twenty-first century enables an individualized approach in the context of predictive, preventive, and personalized medicine that can improve cancer management [18,[61][62][63][64][65][66]. Cancer treatment can also be improved by applying natural substances, which sensitize cancer cells to therapeutic agents [67][68][69][70].…”
Section: Anti-cancer Therapy: From Conventional To Advanced Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further progress in precision medicine in the twenty-first century enables an individualized approach in the context of predictive, preventive, and personalized medicine that can improve cancer management [18,[61][62][63][64][65][66]. Cancer treatment can also be improved by applying natural substances, which sensitize cancer cells to therapeutic agents [67][68][69][70].…”
Section: Anti-cancer Therapy: From Conventional To Advanced Approachesmentioning
confidence: 99%
“…Flavonoids exert numerous biological effects, including antioxidant, anti-inflammatory, anti-mutagenic, and anticancer activities, among others [46]. Although flavonoids have demonstrated significant anti-cancer efficacy in preclinical research [46,69,71,75,76], clinical studies evaluating the anti-cancer effects of flavonoids remain sparse. Genistein was demonstrated to be safe and tolerable in combination with chemotherapy in a recent phase I/II pilot study [43].…”
Section: Flavonoids: Origin and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids are ubiquitous naturally occurring polyphenolic compounds that are commonly found in fruits and vegetables [3]. Flavonoids comprise several classes of low molecular weight compounds, including flavanones, anthocyanidins, flavonols, flavanols, isoflavones, dihydroflavonols, and flavones [4][5][6]. Chrysin (5, 7-dihydroxyflavone, Figure 1) is a natural flavone found in many plant extracts, such as the blue passionflower, as well as in honey and propolis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent updates indicate the multitarget potential of natural products that suggest their strong therapeutic potential against various complex human diseases including cancer and hence use of natural products with multitarget potential would be of great promising therapeutic value. Natural products have showed promising anti-cancer actions via targeting deregulated signaling mechanisms underlying cancer hallmarks including drug resistance, stemness features, metabolic There has been various reports demonstrating how the bioactive molecules, derived from natural products, in combination with conventional chemotherapeutic agents enhance therapeutic outcome with minimal adverse effects (Namdeo et al, 2020;Lin et al, 2020). Generally, combination of natural products gives synergetic and or additive outcome and recently we have also showed that curcumin synergistically enhanced the anticancer action of cisplatin.…”
mentioning
confidence: 99%